UHF propagation along a cargo hold on board a merchant ship - Mao, Xiao Hong (2013)
The characterization of a Line of Sight (LOS) and a Non-Line of Sight (NLOS) link is performed over the military Ultra High Frequency (UHF) band (225 to 450 MHz). This is done using experimental results collected inside the cargo hold of a merchant ship. By analyzing the guiding effect associated with the cargo hold and its sub-structures, the channel characteristics of the environment can be determined. This important propagation mechanism is analyzed using the 3-D ray tracing simulator. Path loss for both topologies is studied and linear path loss models are proposed. Small-scale channel characteristics, such as the number of multipath components, decay factor of the multipath components and Root-Mean-Square (RMS) delay spread are studied and compared for the LOS and NLOS scenarios. Due to the guiding effect and multiple reflections along the cargo hold, both the LOS and NLOS scenarios are found to exhibit similar channel characteristics. A linear decay function is proposed to model the average Power Delay Profiles (PDPs). It is concluded that the linear model provides a good representation for the shape of the impulse responses for a cluttered environment with reflective substructures. This study is useful for the implementation of wireless sensor networks for status monitoring in maritime applications.